'Natural orifice' transcolostomy full-thickness excision of colonic tumour - Victor E Pricolo (Journal of Minimal Access Surgery, 2017)
This technical note describes a novel technique, not previously found in the surgical or endoscopic literature: A combined endoscopic and surgical approach to perform a full-thickness excision of a colonic tumour. At the time of colonoscopy via stoma, a large sessile polyp in the descending colon was detected but could not be safely resected endoscopically. The lesion was exteriorised by prolapsing the distal colon through the colostomy, then excised surgically with adequate margins in a full-thickness fashion. This approach was more complete than an endoscopic approach and less invasive than a segmental colectomy and redo colostomy. It may prove useful to surgical endoscopists facing a similar clinical situation in their practice.